Photodynamic ultradeformable liposomes: Design and characterization - Montanari, J. (2007)
Hydrophobic ([tetrakis(2,4-dimetil-3-pentyloxi)-phthalocyaninate]zinc(II)) (ZnPc) and hydrophilic ([tetrakis(N,N,N-trimethylammoniumetoxi)-phthalocyaninate]zinc(II) tetraiodide) (ZnPcMet) phthalocyanines were synthesized and loaded in ultradeformable liposomes (UDL) of soybean phosphatidylcholine and sodium cholate (6:1, w/w, ratio), resulting 100 nm mean size vesicles of negative Zeta potential, with encapsulation efficiencies of 85 and 53%, enthalpy of phase transition of 5.33 and 158 J/mmol for ZnPc and ZnPcMet, respectively, indicating their deep and moderate partition into UD matrices. Matrix elasticity of UDL-phthalocyanines resulted 28-fold greater than that of non-UDL, leaking only 25% of its inner aqueous content after passage through a nanoporous barrier versus 100% leakage for non-UDL. UDL-ZnPc made ZnPc soluble in aqueous buffer while kept the monomeric state, rendering singlet oxygen quantum yield (fi delta) similar to that obtained in ethanol (0.61), whereas UDL-ZnPcMet had a four-fold higher fi delta than that of free ZnPcMet (0.21). Free phthalocyanines were non-toxic at 1 and 10 microM, both in dark or upon irradiation at 15 J/cm2 on Vero and J-774 cells (MTT assay). Only liposomal ZnPc at 10 microM was toxic for J-774 cells under both conditions. Additionally, endo-lysosomal confinement of the HPTS dye was kept after irradiation at 15 J/cm2 in the presence of UDL-phtalocyanines. This could lead to improve effects of singlet oxygen against intra-vesicular pathogen targets inside the endo-lysosomal system.